Breathing techniques belly and ujjay on declining levels of anxiety in the third trimester of pregnant women - Ratih Kumorojati; Dian Puspitasari; Corry Ocvita Sari (Jurnal Kesehatan Ibu dan Anak, 2020)
Pregnancy and childbirth in a woman is a normal and natural cycle, but the cycle remains a burden for a woman. Mothers who are experiencing pregnancy and want to give birth normally, are required not only to be physically ready, but also to be mentally ready. This study aims to obtain information about the effectiveness of belly and ujjay breathing techniques to reduce anxiety levels in third trimester pregnant women at Klinik Pratama Asih Waluyo Jati, Bantul. This study was a quasi-experimental with two groups of pre-test and post-test with control with a cohort time study approach. The population was third trimester pregnant women in Klinik Pratama Asih Waluyo Jati. The sample was 16 third trimester pregnant women with a sample selection using consecutive sampling techniques. This study uses the Zung Self-Rating Anxiety Scale (ZSAS) anxiety questionnaire, a readiness questionnaire in the face of labor, a checklist of belly breathing techniques and ujjay breathing. Analysis univariate using distribution frequency and bivariate using paired T-test because the data was normally distributed. The univariable analysis was displayed that most respondent was in 20-35 years old (100%), in intermediate education (62.5%) and not working mother (56.2%). The bivariate analyzed results showed in the relaxation group obtained pretest mean 30.06; post test mean 25.94; mean difference 4.12; p-value 0.004 which means there was relaxation of breath in an effective way to reduce anxiety in third trimester pregnant women.